Pemeriksaan SGOT, SGPT dan Jumlah Leukosit Pada Penderita DM Di RSUD Wamena Kabupaten Jayawijaya Papua - Ester Rampa; Herlando Sinaga; Nofiliawati Putri (Poltekkes Kemenkes Mataram, 2021)
Diabetes mellitus is a disease caused by high blood sugar levels due to impaired insulin secretion. Prolonged treatment and therapy carried out by Diabetes Mellitus patients allows damage to the liver, marked by the results of the examination of Serum Glutamic Oxalate Transminase (SGOT) and Serum Glutamic Pyruvit Transminase (SGPT) that are not normal. The purpose of this study was to determine the levels of SGOT, SGPT levels and the number of leukocytes in patients with diabetes mellitus at the Wamena Regional General Hospital, Jayawijaya Regency. This research was conducted from March 13 to June 13, 2019. This type of research is a laboratory test. The population used in this study was Diabetes Mellitus sufferers who conducted an examination at the Wamena Regional General Hospital, Jayawijaya Regency. The samples used were serum and EDTA blood of patients with diabetes mellitus. The method of examining serum glutamic oxalate transminase and serum levels of gltamic pyruvit transminase using Sysmex BX-3010 and the number of leukocytes using the Hematology analyzer Mindray BC-3000 method. The results showed that from a total of 30 patients (100%) the samples studied were 25 SGOT and SGPT normal levels (25%), and were found to have increased SGOT and SGPT levels by 5 patients (16%), while the normal Leukocyte count was 25 patients (84%) and the number of leukocytes increased by 10 patients (34%).